2019
DOI: 10.1590/2175-8239-jbn-2018-0134
|View full text |Cite
|
Sign up to set email alerts
|

Intradialytic resistance training: an effective and easy-to-execute strategy

Abstract: Chronic kidney disease (CKD) alters the morphology and function of skeletal muscles, thereby decreasing patient physical capacity (PC) and quality of life (QoL). Intradialytic resistance training (IRT) is a pragmatic tool used to attenuate these complications. However, IRT has not been strongly adopted in nephrology care centers. This study aimed to assess the efficacy and safety of a low-cost, easy-to-use IRT protocol. Methods: The study enrolled 43 patients (52.8 ± 13.85 years) on HD for five to 300 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
12

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 41 publications
0
11
0
12
Order By: Relevance
“…Intradialytic resistance band exercise training and neuromuscular electrical stimulation were also effective interventions to enhance physical function in patients on HD [ 35 37 ]. It is important to highlight that previous studies have shown exercise interventions are safe and well-tolerated [ 36 ], with no significant changes in hemodynamic parameters [ 38 ] and no adverse events during the training session [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intradialytic resistance band exercise training and neuromuscular electrical stimulation were also effective interventions to enhance physical function in patients on HD [ 35 37 ]. It is important to highlight that previous studies have shown exercise interventions are safe and well-tolerated [ 36 ], with no significant changes in hemodynamic parameters [ 38 ] and no adverse events during the training session [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…André de Castro y colaboradores (22) demostraron que la implementación de un plan de ejercicio anaeróbico intradialítico, durante 39 meses, con ejercicios para dorsales, pectorales, deltoides, cuádriceps, isquiotibiales, pantorrilla, tríceps y bíceps aumenta significativamente la fuerza muscular (de 27,3 [DE: 11,58] a 34,8 kg [DE: 10,77]; p = 0,00). Chan y colaboradores (23) evidenciaron que una intervención intradialítica con ejercicio anaeróbico y de resistencia progresiva durante 12 semanas en la que se considere el esfuerzo percibido por los pacientes y utilice una máquina portátil para la realización de ejercicios de la parte superior e inferior del cuerpo con cargas más pesadas, mientras se ejercitan con pesas de peso libre o bandas elásticas de resistencia los grupos musculares no aislados por el dispositivo de ejercicio, se logra un aumento significativo de la fuerza de agarre en las extremidades inferiores del cuerpo (de 62 [DE: 18,0] a 77 kg [DE: 21,0]; p < 0,0001); sin embargo, no se encontraron cambios significativos en la fuerza de agarre de la extremidad donde era colocada la fístula.…”
Section: Efectos Sobre La Fuerza Muscularunclassified
“…Chang y colaboradores (27) implementaron un programa de ejercicio físico con taichí de estilo corto, de 13 movimientos (ejercicio aeróbico), durante 12 semanas, en el que los pacientes fueron asignados de acuerdo con sus preferencias al grupo E o al grupo C. Como resultado, se observó un aumento significativo (p = 0,00) de la resistencia muscular en el grupo E. La intervención con ejercicios de fuerza-resistencia muscular realizada por Cigarroa y colaboradores (22) dio como resultado un aumento significativo de la fuerza muscular en el miembro inferior derecho (de 223,8 ± 20,3 a 232,9 ± 18,8 puntos; p = 0,02) y en el miembro inferior izquierdo (de 222,3 ± 18,9 a 232,0 ± 18,0 puntos; p = 0,00).…”
Section: Efectos Sobre La Fuerza Muscularunclassified
See 1 more Smart Citation
“…Interventional trials have shown that various forms of supervised programs such as resistance exercise [20, 21], combined aerobic exercise and toning, flexibility and cardiovascular training [22, 23], virtual reality training [24], and Tai-Chi [25] lead to improvements of 0.1–0.3 m/s gait speed in small trials in patients undergoing hemodialysis. Yet, these interventions are difficult to implement in everyone since they tend to be time consuming, need dedicated personnel, and are expensive.…”
Section: Introductionmentioning
confidence: 99%